Esiopetuksen laatu - Backlund-Smulter, Therese; Koivisto, Päivi; Parkkinen, Hely; Sarakorpi, Hanna; Suortti, Outi; Niemelä, Tarja; Kuronen, Ilpo; Knubb-Manninen, Gunnel; Smeds-Nylund, Ann-Sofie; Hietala, Risto; Korkeakoski, Esko; Hujala, Eeva (Koulutuksen arviointineuvoston julkaisuja, ISSN 1795-0155, 2012)
Sammandrag: Kvalitet i förskolundervisningen.
Keywords: opetussuunnitelmat; lapsilähtöisyys; esiopetus; laatu; arviointi; laadunarviointi; förskoleundervisning; kvalitet; kvalitetsbedömning; läroplaner; barnperspektiv